Bis(imidazolium) salts derived from amino acids as receptors and transport agents for chloride anions1. Issue 43 (14th May 2015) - González-Mendoza, Laura; Altava, Belén; Burguete, M. Isabel; Escorihuela, Jorge; Hernando, Elsa; Luis, Santiago V.; Quesada, Roberto; Vicent, Cristian
<x xml:space="preserve">Abstract</x> Binding properties towards different anions and chloride transport activity have been studied using different bis(imidazolium) salts.